2012
DOI: 10.1371/journal.pone.0045713
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of PsbO by the Deg Protease HhoA Is Thioredoxin Dependent

Abstract: The widely distributed members of the Deg/HtrA protease family play an important role in the proteolysis of misfolded and damaged proteins. Here we show that the Deg protease rHhoA is able to degrade PsbO, the extrinsic protein of the Photosystem II (PSII) oxygen-evolving complex in Synechocystis sp. PCC 6803 and in spinach. PsbO is known to be stable in its oxidized form, but after reduction by thioredoxin it became a substrate for recombinant HhoA (rHhoA). rHhoA cleaved reduced eukaryotic (specifically, spin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 81 publications
(136 reference statements)
0
25
0
1
Order By: Relevance
“…However, like the Sec-dependent pathway and unlike the TAT-dependent pathway, these protein export systems require chaperones to prevent premature folding, aggregation and degradation by cytoplasmic proteases [58], [59]. Rex may thus influence protein-assisted export by modulating the distribution pattern of the components of export systems as observed in our proteomic data (Table 2, [60]). In addition, it has been reported that chaperones may be targets for intracellular ROS [61].…”
Section: Discussionmentioning
confidence: 79%
“…However, like the Sec-dependent pathway and unlike the TAT-dependent pathway, these protein export systems require chaperones to prevent premature folding, aggregation and degradation by cytoplasmic proteases [58], [59]. Rex may thus influence protein-assisted export by modulating the distribution pattern of the components of export systems as observed in our proteomic data (Table 2, [60]). In addition, it has been reported that chaperones may be targets for intracellular ROS [61].…”
Section: Discussionmentioning
confidence: 79%
“…The N‐terminus of PsbO forms a tail‐like structure containing a small α‐helix that is attached to the β‐barrel by a conserved disulfide bond (De Las Rivas and Barber , Nikitina et al ). This disulfide bond is involved in redox regulation of chloroplast proteins (Buchanan et al ) via processes such as oxidative folding in the lumen (Kieselbach ) and thioredoxin‐dependent degradation of PsbO (Roberts et al ).…”
Section: Introductionmentioning
confidence: 99%
“…PsbO therefore has both rigid and fluid parts, giving it both stability and high flexibility. This allows PsbO to respond dynamically to changes in the abundance of redox‐active thioredoxin (Roberts et al ), pH (Shutova et al , , , Bommer et al ), GTP (Lundin et al ) and the calcium ions (Heredia and De Las Rivas , Shutova et al , Murray and Barber ). The structural dynamics of PsbO have been analyzed and related to its functional role in photosynthetic water oxidation based on experiments using intra‐molecular cross‐linking (Enami et al ) and FTIR spectroscopy (Hutchison et al , Sachs et al , Offenbacher et al ).…”
Section: Introductionmentioning
confidence: 99%
“…PCC 6803 encodes three HtrA-family genes, slr1204/htrA, sll1679/hhoA, and sll1427/hhoB [14]. Physiological roles such as preventing the accumulation of oxidized proteins and protecting from light stress have been attributed to them [15][16][17][18][19][20]. These three Synechocystis HtrA-family members notably differ from their chloroplast homologs in that they do not participate in degradation of the D1 protein of photosystem II [21].…”
mentioning
confidence: 99%